Enhancement of Electrical and Optical Properties of Sodium Bromide Doped Carboxymethyl Cellulose Biopolymer Electrolyte Films. Issue 4 (2nd April 2020) - Shetty, Supriya K; Ismayil,; Shetty, Gowtham
Abstract: Biodegradable ion conducting solid polymer electrolyte films of carboxymethyl cellulose (CMC) doped with sodium bromide (NaBr) with various weight percentages were prepared by a solution casting technique. Their structural, optical and electrical properties were studied by various experimental techniques in order to understand the impact of the sodium metal salt on the biopolymer CMC's properties. The optical parameters namely the optical bandgap energy and the refractive index, showed a significant variable variation with the metal salt concentration. The maximum dc conductivity was found to be ∼5.15 × 10 −4 S cm −1 at room temperature for the sample with 20 wt% of NaBr content in the CMC matrix. The ionic conductivity and dielectric constant in general, increased with increase in metal salt content, affirming the increase in ion concentration. The calculated transference number showed that the conductivity was mainly due to ions. The increase in conductivity was due to an increase in degree of amorphousness of the polymer upon doping, as analyzed by their XRD spectra.